2011
DOI: 10.1093/annonc/mdq757
|View full text |Cite
|
Sign up to set email alerts
|

Src: a potential target for the treatment of triple-negative breast cancer

Abstract: We conclude that dasatinib with cisplatin is a rational drug combination for testing in triple-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 22 publications
11
99
1
2
Order By: Relevance
“…However, Src inhibitor alone does not appear to achieve therapeutic effects in clinical trials. Finn et al demonstrated that the Src family inhibitor dasatinib alone showed only limited anticancer effects in a phase II clinical trial of triple negative breast cancer patients (38); combination with chemotherapy medication may improve the therapeutic effects (39). Our results also suggested that P4+PP1 combined treatment significantly inhibited the migration and invasion of lung adenocarcinoma A549 cells; P4 or PP1 alone showed limited effects.…”
Section: Molecular Pathways Involved In P4+pp1/mprα Signalingsupporting
confidence: 60%
“…However, Src inhibitor alone does not appear to achieve therapeutic effects in clinical trials. Finn et al demonstrated that the Src family inhibitor dasatinib alone showed only limited anticancer effects in a phase II clinical trial of triple negative breast cancer patients (38); combination with chemotherapy medication may improve the therapeutic effects (39). Our results also suggested that P4+PP1 combined treatment significantly inhibited the migration and invasion of lung adenocarcinoma A549 cells; P4 or PP1 alone showed limited effects.…”
Section: Molecular Pathways Involved In P4+pp1/mprα Signalingsupporting
confidence: 60%
“…Because kinases are crucial for cancer cell survival, mitosis, migration and invasion, much research has been focused on developing inhibitors against them (6)(7)(8). Rapidly proliferating tumors like TNBCs rely on tight temporal regulation of the cell cycle and centrosome duplication.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, a number of studies have demonstrated that SRC, Raf, and VEGFR2 could be potential targets for the treatment of TNBC (13,18,34,35). The SRC/Raf inhibitor, SKLB646, indeed showed a nice selective inhibition of TNBC cell lines bearing an overexpression of SRC and mutant Raf, MD-MB-231, and MD-MB-435 (36,37).…”
Section: Discussionmentioning
confidence: 96%
“…Abnormal activation or amplification of SRC has been detected in TNBC and demonstrated to play a role in proliferation, migration, and invasion of breast cancer cell lines (11,12). Furthermore, a number of recent studies have shown that dysregulation of SRC is strongly associated with tumor metastasis and poor prognosis in TNBC (13,14). SRC therefore represents a rational molecular target for TNBC.…”
Section: Introductionmentioning
confidence: 99%